Association between nutritional inflammation index and diabetic foot ulcers: a population-based study - Lin, Zhou; Zhuang, Wanli; Wang, Lei; Lan, Weifeng (Frontiers in Nutrition, 2025)
BackgroundDiabetic foot ulcers (DFU), a frequent complication of the worldwide disease (diabetes), are the primary causes of amputations and early mortality. The development of DFU is inseparably linked with inflammation and nutrition, necessitating a comprehensive evaluation of their impact on DFU risk. This study aimed to establish a new predictive metric that integrated immune inflammation and nutritional markers to holistically assess the risk of DFU development.MethodsData were sourced from NHANES, extracting participant from 1999 to 2004. Analysis of multivariate logistic regression and restricted cubic spline were employed to elucidate the connection and non-linear relationship between albumin/neutrophil to lymphocyte ratio (ANLR) and DFU. Stratified subgroup analysis identified advantageous populations, while interaction analysis evaluated variable interactions with ANLR. These approaches collectively contributed to a sensitivity analysis, improving the reliability of the outcomes.ResultsOut of 29,608 participants extracted, 1,531 qualified based on the study criteria. Employing the ANLR low group as a reference, the high group demonstrated a 54% reduction in DFU risk. Every increase of 0.1 unit in ANLR correlated with a 5% decrease in DFU risk. Moreover, an L-shaped non-linear link was observed. The turning point was at 3.09. Left of the inflection point, the relationship was negatively correlated. Beyond this point, further increased in ANLR no longer decrease DFU risk.ConclusionThe study not only proposed a new comprehensive indicator for predicting DFU for the first time but also specified the impact of ANLR on DFU risk. Broadly, a negative correlation existed between the two. Yet, a detailed analysis revealed that this negative correlation involved an inflection point effect. Furthermore, the study investigated how dynamic changes in ANLR affect DFU risk, aiding clinicians in more accurately assessing individual DFU risk and facilitating earlier identification and intervention of DFU. Therefore, for diabetic patients with low serum albumin, appropriate supplementation of albumin was crucial. Additionally, maintaining the NLR at an appropriate level should not be overlooked. Given the components of ANLR were widely used and readily available in clinical settings, their future clinical applications hold great potential.